The impact of coronavirus disease 2019 (COVID-19) on liver injury in China: A systematic review and meta-analysis. Issue 4 (29th January 2021) - Zhao, Xin; Lei, Zehua; Gao, Fengwei; Xie, Qingyun; Jang, Kangyi; Gong, Jie
Abstract: Introduction: The evidence for the incidence and severity of liver injury in Chinese patients with coronavirus disease 2019 (COVID-19) is still controversial. The purpose of this study was to summarize the incidence of liver injury and the differences between liver injury markers among different patients with COVID-19 in China. Methods: Computer searches of PubMed, Embase, China National Knowledge Infrastructure (CNKI) and medRxiv were used to obtain reports on the incidence and markers of liver injury in Chinese patients with COVID-19, from January 1, 2020 to April 10, 2020. (No. CRD42020181350) Results: A total of 57 reports from China were included, including 9889 confirmed cases of COVID-19 infection. The results of the meta-analysis showed that among the patients with early COVID-19 infection in China, the incidence of liver injury events was 24.7% (95% CI, 23.4%–26.4%). Liver injury in severe patients was more common than that in non-severe patients, with a risk ratio of 2.07 (95% CI, 1.77–2.43). Quantitative analysis showed that the severe the coronavirus infection, the higher the level of alanine aminotransferase (ALT), aspertate aminotransferase (AST), total bilirubin (TB), alkaline phosphatase (ALP), γ-glutamyl transpeptidase (GGT), and the lower the level of albumin (ALB). Conclusion: There is a certain risk of liver injury in Chinese patients with COVID-19, and the risk and degree of liver injury are related to the severity of COVID-19.